The role of the polypyrimidine stretch at the SV40 early pre-mRNA 3' splice site in alternative splicing. - Fu, X Y (1988)
We have studied the role in pre-mRNA splicing of the nucleotide sequence preceding the SV40 early region 3' splice site. Somewhat surprisingly, neither the pyrimidine at the highly conserved -3 position, nor the polypyrimidine stretch that extends from -5 to -15, relative to the 3' splice site, were found to be required for efficient splicing. Mutations that delete this region or create polypurine insertions at position -2 had no significant effects on the efficiency of SV40 early pre-mRNA splicing in vivo or in vitro. Interestingly, however, the pyrimidine content of this region had substantial effects on the alternative splicing pattern of this pre-mRNA in vivo. Mutations that increased the number of pyrimidine residues resulted in more efficient utilization of the large T antigen mRNA 5' splice site relative to the small t 5' splice site, while mutations that increased the purine content enhanced small t mRNA splicing. A possible molecular mechanism for these findings, as well as a model that proposes a role for the polypyrimidine stretch in alternative splicing, are discussed.